Voluntary errors as causes of challenge in the employment relationship. - Nádas, György; Prugberger, Tamás (European Integration Studies, 2023)
The study covers two main topics. The first part of the study deals with the avoidance of the statement on commitment relating to relating to employment. Thus, the Hungarian Labour Code, in contrast to the provisions of the Hungarian Civil Code, assures a quite short period for the avoidance of the statement, in case of coercion, threat, mistake or mislead. In the opinion of the author, this special, shorter period is not justified. In the second part of the study, the author proposes to handle employment-related legal acts similarly to consumer contracts, since labour contracts are mostly concluded by using contract form. Moreover, the author suggests extending the application of collective action (actio popularis) to these labour contracts.